Buffered high charge spectrally-peaked proton beams in the relativistic-transparency regime. (18th January 2016) - Dover, N P; Palmer, C A J; Streeter, M J V; Ahmed, H; Albertazzi, B; Borghesi, M; Carroll, D C; Fuchs, J; Heathcote, R; Hilz, P; Kakolee, K F; Kar, S; et al.
Abstract: Spectrally-peaked proton beams of high charge (, , nC ) have been observed from the interaction of an intense laser ( W cm −2 ) with ultrathin CH foils, as measured by spectrally-resolved full beam profiles. These beams are reproducibly generated for foil thicknesses 5–100 nm, and exhibit narrowing divergence with decreasing target thickness down to for 5 nm. Simulations demonstrate that the narrow energy spread feature is a result of buffered acceleration of protons. The radiation pressure at the front of the target results in asymmetric sheath fields which permeate throughout the target, causing preferential forward acceleration. Due to their higher charge-to-mass ratio, the protons outrun a carbon plasma driven in the relativistic transparency regime.